2021
DOI: 10.1002/pbc.29055
|View full text |Cite
|
Sign up to set email alerts
|

MYH9 disorder: Identification and a novel mutation in patients with macrothrombocytopenia

Abstract: The diagnosis of MYH9 disorder is guided by recognizing granulocyte Döhle body-like inclusion bodies and large/giant platelets in the peripheral blood smear. Immunofluorescence study of nonmuscle myosin heavy chain IIA is a sensitive screening method for diagnosis of MYH9 disorder. The diagnosis can then be confirmed by genetic analysis. A total of 67 patients with macrothrombocytopenia were included, of which 11 patients (16%), aged 4 months to 22 years, were ultimately diagnosed with MYH9 disorder. One novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…10 Döhle-like bodies are relatively easy to detect in the coil/tail variant group compared to the head variant group. [19][20][21] This information suggests that detectable Döhle-like bodies in the coil/ tail variants play an important role as a trigger to suspect MYH9-RD. Furthermore, we have previously reported that IPF% can be an adjunctive diagnostic factor, as IPF% is high at any variant site.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…10 Döhle-like bodies are relatively easy to detect in the coil/tail variant group compared to the head variant group. [19][20][21] This information suggests that detectable Döhle-like bodies in the coil/ tail variants play an important role as a trigger to suspect MYH9-RD. Furthermore, we have previously reported that IPF% can be an adjunctive diagnostic factor, as IPF% is high at any variant site.…”
Section: Discussionmentioning
confidence: 92%
“…RNA content is responsible for the morphological appearance of conventionally stained blood films and the amount of RNA is decreased in head variants 10 . Döhle‐like bodies are relatively easy to detect in the coil/tail variant group compared to the head variant group 19–21 . This information suggests that detectable Döhle‐like bodies in the coil/tail variants play an important role as a trigger to suspect MYH 9‐RD.…”
Section: Discussionmentioning
confidence: 95%